Guideline for Antimicrobial Prophylaxis in Breast Surgery - Sema Bağhaki; Gürsel Remzi Soybir; Atilla Soran (European Journal of Breast Health, 2014)

(untitled)
The American Society of Health-System Pharmacists (ASHP) published the 2012/2013 edition of the book entitled “Best Practices for Hospital&Health-System Pharmacy: Position and Guidance Documents of ASHP” with Bruce Hawkins as the editor (ISSN: 15558975). Pages 582-667 of this book contain the section:”Therapeutic Guidelines on Antimicrobial Prophylaxis in Surgery”. This section includes current clinical developments, evidence and recommendations on the application of standard and effective antimicrobial prophylaxis in adult and pediatric patients, and has significant differences compared to the previous 1999 edition. On pages 632-633, antimicrobial prophylaxis in breast and plastic surgery practice is addressed in detail. This article contains a summary of the recommendations made in ASHP 2012/2013 Report regarding the antimicrobial prophylaxis in breast and plastic surgery applications.